1998
DOI: 10.1103/physrevlett.80.4891
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Ionospheric Preconditioning and Stimulated Electromagnetic Radiation

Abstract: New results of stimulated electromagnetic emissions (SEE) from the HIPAS Observatory are reported. A novel hf heating sequence was used to first precondition the ionosphere, and SEE was then excited with low-amplitude test pulses. Through this approach, the nonlinear physics of SEE was studied. The correlation between small-scale field-aligned density striations and SEE generation was demonstrated, and SEE was excited at power density of 24 dB less than normally required. The results compare well with theoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Experimental observations have shown that most of the SEE spectral characteristics depend on the pump frequency ( f 0 ) in relation to the F‐region electron cyclotron frequency ( f ce ) [ Leyser et al , 1989, 1990; Stubbe et al , 1994; Honary et al , 1999; Cheung et al , 1998] and/or F‐region critical frequency [ Leyser et al , 1990; Armstrong et al , 1990]. The first classification of the SEE spectral features was performed by Stubbe et al [1984] who categorized them either as “gyrofeatures” which exist only at f 0 ≈ nf ce , where electron gyroharmonic number n = 3 or greater, such as the up‐shifted maximum (UM), or universal features, which exist at all frequencies except for pumping close to a gyroharmonic, for example, the down‐shifted maximum (DM).…”
Section: Stimulated Electromagnetic Emissions: the Broad Up‐shifted Mmentioning
confidence: 99%
“…Experimental observations have shown that most of the SEE spectral characteristics depend on the pump frequency ( f 0 ) in relation to the F‐region electron cyclotron frequency ( f ce ) [ Leyser et al , 1989, 1990; Stubbe et al , 1994; Honary et al , 1999; Cheung et al , 1998] and/or F‐region critical frequency [ Leyser et al , 1990; Armstrong et al , 1990]. The first classification of the SEE spectral features was performed by Stubbe et al [1984] who categorized them either as “gyrofeatures” which exist only at f 0 ≈ nf ce , where electron gyroharmonic number n = 3 or greater, such as the up‐shifted maximum (UM), or universal features, which exist at all frequencies except for pumping close to a gyroharmonic, for example, the down‐shifted maximum (DM).…”
Section: Stimulated Electromagnetic Emissions: the Broad Up‐shifted Mmentioning
confidence: 99%
“…L wave pumping of the long predicted localized UH oscillations [ Vas'kov and Gurevich , 1976; Dysthe et al , 1982; Gurevich et al , 1995; Istomin and Leyser , 1997] provides a unified interpretation for a range of experimental results, including pump beam self‐focusing in geomagnetic zenith, annular optical emission regions and equatorward displacement of the excitation region. Localized UH oscillations have previously been detected indirectly in stimulated electromagnetic emissions during controlled ionospheric preconditioning experiments [ Cheung et al , 1998].…”
Section: Introductionmentioning
confidence: 99%
“…It was discovered experimentally already in 1981 that when a narrow-band high-frequency (hf) radio beam of high intensity irradiates the ionosphere at a frequency f 0 which is close to the local ionospheric plasma frequency f p , a structured, wide-band secondary radiation escapes from the interaction region [1], a phenomenon now known as stimulated electromagnetic emission (SEE) [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. By varying the injected hf beam systematically in terms of frequency, intensity, and duty cycle and analyzing the secondary radiation, and hence the associated hf radio beam-excited ionospheric plasma turbulence and wave conversion processes, we have been able to study the competition between the effects due to ponderomotive parametric instabilities (PPI) [22 -24] and those due to thermal parametric instabilities (TPI) [25,26].…”
mentioning
confidence: 99%